Lectins from Synadenium carinatum (ScLL) and Artocarpus heterophyllus (ArtinM) Are Able to Induce Beneficial Immunomodulatory Effects in a Murine Model for Treatment of Toxoplasma gondii Infection - , Leandro Peixoto Ferreira de Souza; Ramos, Eliézer L. P.; Santana, Silas S.; Silva, Murilo V.; Santiago, Fernanda M.; Mineo, Tiago W. P.; Mineo, José R. (Frontiers in Cellular and Infection Microbiology, 2016)
Infection by Toxoplasma gondii affects around one-third of world population and the treatment for patients presenting toxoplasmosis clinically manifested disease is mainly based by a combination of sulfadiazine, pyrimethamine and folinic acid. However, this therapeutic protocol is significantly toxic, causing relevant dose-related bone marrow damage. Thus, it is necessary to improve new approaches to investigate the usefulness of more effective and non-toxic agents for treatment of patients with toxoplasmosis. It has been described that lectins from plants can control parasite infections, when used as immunological adjuvants in vaccination procedures. This type of lectins, such as ArtinM and ScLL is able to induce immunostimulatory activities, including efficient immune response against parasites. The present study aimed to evaluate the potential immunostimulatory effect of ScLL and ArtinM for treatment of T. gondii infection during acute phase, considering that there is no study in the literature accomplishing this issue. For this purpose, bone marrow-derived macrophages (BMDMs) were treated with different concentrations from each lectin to determine the maximum concentration without or with lowest cytotoxic effect. After, it was also measured the cytokine levels produced by these cells when stimulated by the selected concentrations of lectins. We found that ScLL showed high capacity to induce of pro-inflammatory cytokine production, while ArtinM was able to induce especially an anti-inflammatory cytokines production. Furthermore, both lectins were able to increase NO levels. Next, we evaluated the treatment effect of ScLL and ArtinM in C57BL/6 mice infected by ME49 strain from T. gondii. The animals were infected and treated with ScLL, ArtinM, ArtinM plus ScLL or sulfadiazine, and the following parameters analyzed: cytokines production, brain parasite burden and survival rates. Our results demonstrated that the ScLL or ScLL plus ArtinM treatment induced production of pro-inflammatory and anti-inflammatory cytokines, showing differential but complementary profiles. Moreover, when compared with non treated mice, the parasite burden was significantly lower and survival rates higher in mice treated with ScLL or ScLL plus ArtinM, similarly with sulfadiazine treatment. In conclusion, the results demonstrated the suitable potential immunotherapeutic effect of ScLL and ArtinM lectins to control acute toxoplasmosis in this experimental murine model.